2022
DOI: 10.1021/acsami.2c02061
|View full text |Cite
|
Sign up to set email alerts
|

Intrinsically Breathable and Flexible NO2 Gas Sensors Produced by Laser Direct Writing of Self-Assembled Block Copolymers

Abstract: The surge in air pollution and respiratory diseases across the globe has spurred significant interest in the development of flexible gas sensors prepared by low-cost and scalable fabrication methods. However, the limited breathability in the commonly used substrate materials reduces the exchange of air and moisture to result in irritation and a low level of comfort. This study presents the design and demonstration of a breathable, flexible, and highly sensitive NO2 gas sensor based on the silver (Ag) decorated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
49
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 65 publications
(49 citation statements)
references
References 52 publications
0
49
0
Order By: Relevance
“…19 Other recent advances in LIG processing technology include the use of modified threedimensional (3D) printing processes derived from laminated object manufacturing to make 3D LIG foams, 20,21 substituting the CO 2 laser for visible light and UV laser sources to scribe LIG, 22,23 using laser direct writing technologies to fabricate LIG, 24 and monolithic fabrication processes, 25 among others. 26,27 Here we show that various artistic LIG designs can also be embedded into the composite material of concrete and tailored to their desired application. For solely aesthetic applications, LIG composite (LIGC) designs were tailored to demonstrate the precision and detail of the LIG lasing and grafting process.…”
Section: Introductionmentioning
confidence: 86%
See 1 more Smart Citation
“…19 Other recent advances in LIG processing technology include the use of modified threedimensional (3D) printing processes derived from laminated object manufacturing to make 3D LIG foams, 20,21 substituting the CO 2 laser for visible light and UV laser sources to scribe LIG, 22,23 using laser direct writing technologies to fabricate LIG, 24 and monolithic fabrication processes, 25 among others. 26,27 Here we show that various artistic LIG designs can also be embedded into the composite material of concrete and tailored to their desired application. For solely aesthetic applications, LIG composite (LIGC) designs were tailored to demonstrate the precision and detail of the LIG lasing and grafting process.…”
Section: Introductionmentioning
confidence: 86%
“…As the concentration of polymer increases, the role the composite polymer material plays in surface functionality increases while the surface properties of the LIG decreases. , Interestingly, the use of LIG to pattern paper surfaces has been suggested as a new tool for generating artistic designs on paper substrates, and the electrical conductivity of LIG might lead to additional in-built functionality . Other recent advances in LIG processing technology include the use of modified three-dimensional (3D) printing processes derived from laminated object manufacturing to make 3D LIG foams, , substituting the CO 2 laser for visible light and UV laser sources to scribe LIG, , using laser direct writing technologies to fabricate LIG, and monolithic fabrication processes, among others. , …”
Section: Introductionmentioning
confidence: 99%
“…Traditional electronic sensors usually use rigid substrates, which cannot meet wearable requirements, while flexible sensors have attracted wide attention due to their advantages of small size, high sensitivity, comfortable wearing, and excellent fit to the skin. , Therefore, flexible sensors can monitor the physiological signals of the wearer . Cheng and co-workers proposed a method to directly fabricate electronic devices on freeform surfaces using intense pulsed light-induced mass transfer, and deploying functional circuits on 3D freeform surfaces has greatly promoted the development of flexible wearable devices .…”
Section: Introductionmentioning
confidence: 99%
“…The selection of high-quality active materials and expansion of the contact area are the most important ways to obtain high-sensitivity pressure sensors. , On the one hand, two-dimensional (2D) materials have shown good performance advantages in the field of pressure sensors . As a 2D material similar to graphene, MXene has been widely used in energy storage devices, sensors (such as gas sensors, mechanical sensors , ), and electromagnetic shielding devices, due to its rich chemical composition, tunable surface termination, excellent metal conductivity, and good surface hydrophilicity. Moreover, MXene is also popular in the research of pressure sensors because the large specific surface area of MXene effectively increases the binding force with the substrate, resulting in excellent mechanical properties . Recently, Guo et al reported a fabric pressure sensor based on MXene coating .…”
Section: Introductionmentioning
confidence: 99%
“…Structural transformation that mainly involves inducing defects implantation [104], carbonization [105] and laser direct writing [106] is an efficient and practical way to produce conductive fibers. Defects implantation is a method in which the electron bonding and band structure are tuned in variant degrees by different types of defects produced in various sites of metal oxides lattices, resulting in notable changes of metal oxides in optical, electrical, magnetic and thermal properties [107].…”
Section: Structural Transformationmentioning
confidence: 99%